Analisis Sentimen dan Jaringan Komentar Video YouTube Kompas TV Debat Pertama Cawapres pada Pilpres 2024 - Syifa Ayu Salsabilla; Gema Nusantara Bakry; FX. Ari Agung Prastowo (CV. Creative Tugu Pena, 2024)
The 2024 Presidential Election (Pilpres) in Indonesia is an important moment involving a debate on the vice presidential candidates (Cawapres). This research aims to analyze the sentiment and comment network on the Cawapres debate video on YouTube KompasTV using the Social Network Analysis (SNA) approach. Data collected from YouTube comments, analyzed using Netlytic and Gephi to identify public sentiment and key actors. The results show that interaction between actors is relatively easy with the dominance of positive comments. The word